2023
DOI: 10.2196/48905
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Substance Use via Reddit: Systematic Scoping Review

Yu Chi,
Huai-yu Chen

Abstract: Background Reddit’s (Reddit Inc) large user base, diverse communities, and anonymity make it a useful platform for substance use research. Despite a growing body of literature on substance use on Reddit, challenges and limitations must be carefully considered. However, no systematic scoping review has been conducted on the use of Reddit as a data source for substance use research. Objective This review aims to investigate the use of Reddit for studying … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 94 publications
0
6
0
Order By: Relevance
“…Past research has suggested that Reddit is a popular social media platform well suited for substance-related research due to its large number of users with diverse backgrounds, which facilitates longitudinal data analysis and insights into the evolving nature of substance use and discussions [ 30 ]. Various studies have indicated that engaging in substance-related discussions can be a strong marker of an individual’s experience with substance use [ 26 , 28 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Past research has suggested that Reddit is a popular social media platform well suited for substance-related research due to its large number of users with diverse backgrounds, which facilitates longitudinal data analysis and insights into the evolving nature of substance use and discussions [ 30 ]. Various studies have indicated that engaging in substance-related discussions can be a strong marker of an individual’s experience with substance use [ 26 , 28 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…Various studies have indicated that engaging in substance-related discussions can be a strong marker of an individual’s experience with substance use [ 26 , 28 , 31 ]. For our data set, we focus on Reddit, a prevalent social media platform where individuals can anonymously participate in topic-centered communities known as “subreddits.” Each subreddit operates under its own set of rules to moderate posts and comments, offering unfiltered discussions with less interference from overarching platform policies, distinguishing Reddit as an ideal platform for analysis of substance-related conversations [ 30 ]. On Reddit, there are various subreddits dedicated to discussing different substances, such as cannabis, cocaine, and fentanyl, as well as behaviors associated with these substances, such as active misuse, harm reduction, and recovery.…”
Section: Methodsmentioning
confidence: 99%
“…This indicates that, although OHCs often include patients that are typically excluded from clinical trials (such as those with multiple conditions), studying these communities is useful to understand patient populations [51]. Indeed, content analysis of these communities reveals patterns across patients' experiences of care and symptoms [52][53][54][55] and OHC members' expertise in providing support to peers could be leveraged to deliver healthcare interventions and programs [41,43,50,56].…”
Section: Online Health Communitiesmentioning
confidence: 99%
“…We envisaged that we would identify a wider array of symptom management techniques on r/ADHD than earlier work using conventional research designs (e.g., qualitative interviews and psychometric assessments), which would require expanded categorization. This was informed by the anonymous nature of r/ADHD in allowing for open and instantaneous exchanges, as has been noted for various subreddits [31]. Equally, the inclusion of longitudinal data up to 2023 might have captured emerging strategies or social shifts not represented in earlier, cross-sectional analyses.…”
Section: The Present Studymentioning
confidence: 99%
“…Reddit and r/ADHD dynamics Several community-specific factors could have influenced the types of compensation strategies represented on r/ADHD. Notably, the anonymous nature of Reddit allows for candid dialogues [31]. Yet, it is conceivable that users remained reluctant to describe certain compensation strategies on a publicly-accessible platform, albeit under a pseudonymous username.…”
Section: R/adhd Compensation Strategies and Covid-19mentioning
confidence: 99%